Present-day interseismic deformation characteristics of the Beng Co-Dongqiao conjugate fault system in central Tibet: implications from InSAR observations. Issue 1 (8th January 2020) - Yongsheng, Li; Yunfeng, Tian; Chen, Yu; Zhe, Su; Wenliang, Jiang; Zhenhong, Li; Jingfa, Zhang; Yi, Luo; Bingquan, Li
SUMMARY: Numerous V-shaped conjugate strike-slip fault systems distributed between the Lhasa block and the Qiangtang block serve as some of the main structures accommodating the eastward motion of the Tibetan Plateau. The Beng Co-Dongqiao conjugate fault system is a representative section, and determining its tectonic environment is a fundamental issue for understanding the dynamic mechanism of the V-shaped conjugate strike-slip fault systems throughout central Tibet. In this paper, we investigate the deformation rates of the Beng Co-Dongqiao conjugate faults using 3 yr of SAR data from both ascending and descending tracks of Sentinel-1 satellites. Only interferograms with a long temporal baseline were used to increase the proportion of the deformation signals. The external atmospheric delay product and the InSAR stacking strategy were employed to reduce various errors in the large-spatial-coverage Sentinel-1 data. The InSAR results revealed that the fault-parallel deformation velocities along the eastern and western segments of the Beng Co fault are 5 ± 1 mm/yr and 2.5 ± 1 mm/yr, respectively. The second invariant of the horizontal strain rates shows that the accumulated strain is centered on the eastern segment of the Beng Co Fault and Gulu rift. The velocity and strain rate fields show that the Anduo-Peng Co faults may be paired with the Beng Co fault to form a new conjugate system and the tectonic transformation between the Beng Co fault and Gulu rift. These results can better explain the tectonic deformation environment of the Beng Co-Dongqiao conjugate fault system and provide insights on the crustal dynamics throughout the entire plateau interior.